THE ROLE OF SCHOENOPLECTUS TRIQUETER IN ENSURING ECOSYSTEM STA-BILITY: ITS MEDICINAL AND ECOLOGICAL SIGNIFICANCE (Scientific journal of the Fergana State University, 2026)
This article examines the distribution areas of Schoenoplectus triqueter (Scirpus triqueter), its ecological functions, and the biologically active compounds present in its chemical composition. During the study, the role of this species as a natural biofilter in improving water quality and maintaining ecosystem stability was analyzed. The chemical composition of extracts obtained from the roots and stems of the plant was determined, revealing the presence of flavonoids, phenolic compounds, polysaccharides, organic acids, and carbohydrates. In addition, the antioxidant, antibacterial, and cytotoxic properties of the extracts were identified, with particular emphasis on their selective effects against A549 lung cancer cells. The findings highlight the ecological significance of Schoenoplectus triqueter in terms of environmental protection and demonstrate its potential as a promising raw material for the pharmaceutical industry.